1987
DOI: 10.1104/pp.85.2.419
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Quantitation of Indole 3-Acetic Acid and Abscisic Acid in Small Samples of Plant Tissue by Gas Chromatography/Mass Spectrometry/Selected Ion Monitoring

Abstract: Indole 3-acetic acid (IAA) was analyzed in apple, orange, and prune tissue by GC-MS by monitoring the protonated molecular ion of its methyl ester at mass to charge ratio (m/z) 190 together with the major fragment ion at m/z 130 and the corresponding ions from the methyl esters of either 12H4JIAA (m/z 194, 134) or I2HS5IAA (m/z 195, 135).Abscisic acid (ABA) was analyzed by monitoring the major fragment ions of its methyl ester at m/z 261 and m/z 247 and the corresponding ions from the methyl ester of rH31ABA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…The ABA was determined from traces at m/z 162, 166, 190, and 194 using the isotope dilution equation described for IAA (3). Radiolabeled internal standards were used to estimate recoveries of the target compounds (1) and confirmed according to procedures presented by Vine et al (19) (19). The aqueous residue left after rotary flash evaporation as described in the section on sample preparation was adjusted to a pH of 8.5 with a saturated solution of NaHCO3 and partitioned 3 times against equal volumes of petroleum ether followed by 3 equal volumes of diethyl ether.…”
Section: Gc-sim-ms Analysismentioning
confidence: 99%
“…The ABA was determined from traces at m/z 162, 166, 190, and 194 using the isotope dilution equation described for IAA (3). Radiolabeled internal standards were used to estimate recoveries of the target compounds (1) and confirmed according to procedures presented by Vine et al (19) (19). The aqueous residue left after rotary flash evaporation as described in the section on sample preparation was adjusted to a pH of 8.5 with a saturated solution of NaHCO3 and partitioned 3 times against equal volumes of petroleum ether followed by 3 equal volumes of diethyl ether.…”
Section: Gc-sim-ms Analysismentioning
confidence: 99%
“…GC-MS provides precise measurements of small amounts of IAA, with the accuracy of each estimate being checked by comparing response ratios of several characteristic fragments (Cohen et al, 1986). However, as with other methods, several purification steps are needed if accurate quantitative estimates of IAA in plant extracts are to be obtained (Rivier, 1986;Vine et al, 1987;Chen et al, 1988;Dunlap and Guinn, 1989). By using a double-focusing HR mass spectrometer, the selectivity of the analysis increases and overcomes some of the problems caused by interfering substances.…”
mentioning
confidence: 99%
“…
ABSTRACTEster conjugates of indole-3-acetic 16,18,22,23) following various protocols suggested that a more systematic evaluation of this process was needed. In this report we present data on the kinetics of hydrolysis of reagent IAA-GLU2 at selected pH values and compare the lability of IAA-GLU to that of IAA-MI and several other ester conjugates of IAA.
…”
mentioning
confidence: 99%